Intramyocardial haematoma causing right ventricular outflow obstruction after brown snake (Pseudonaja species) envenomation in a dog. Issue 9 (8th July 2020) - Kang, K; Sharp, CR; Boyd, CJ; Turner, K
Abstract : A 15‐month‐old, male neutered Staffordshire Bull Terrier cross was presented to its referring veterinarian collapsed and agonal. He was immediately intubated, manually ventilated, and treatment commenced for presumptive snake envenomation with two vials of Tiger/Multi‐Brown Snake Antivenom (minimum 7000 units/vial). The dog was transferred to a referral hospital intubated. Additional diagnostics performed following arrival at the referral hospital included a urine snake venom detection kit test, which was positive for brown snake immunotype. Three additional vials of Tiger/Multi‐Brown Snake Antivenom (minimum 7000 units/vial) were administered until the dog was extubated and able to stand. Venom‐induced consumptive coagulopathy (VICC) was diagnosed based on prolonged clotting times and scleral haemorrhage. Paroxysms of right ventricular outflow tract (RVOT) origin ventricular arrhythmias were treated with lignocaine and sotalol. Four days after presentation, a new‐grade IV/VI systolic heart murmur was auscultated, prompting an echocardiogram. An anechoic and compartmentalised mass measuring 43 mm × 19 mm was visualized within the right ventricular wall at the RVOT, immediately adjacent to the pulmonic valve. The mass was causing a RVOT obstruction. Its appearance was suggestive of an intramyocardial haematoma, most likely secondary to VICC. The dog remained cardiovascularly stable, and treatment consisted of supportive care. Recheck echocardiograms at 2 and 7 weeks after discharge revealed progressive improvement of the intramyocardial mass and resolution of the associated heart murmur. Although intramyocardial haematomas are rare, it should be considered as a differential in dogs that develop a newly diagnosed heart murmur and/or cardiac arrhythmia following brown snake envenomation.